Flame Spray Synthesis of VOPO4 Polymorphs - Jodhani, Gagan; Mikaeili, Fateh; Gouma, Pelagia Irene (Frontiers in Materials, 2019)
VOPO4 is a polymorphic compound that exhibits excellent catalytic and electronic properties. Here, formation of different VOPO4 polymorphs using two different organic compounds as precursors is investigated for the first time using flame spray pyrolysis as an alternative method to hydrothermal synthesis of VOPO4, the only method currently known for its synthesis. Ammonium-based salts of vanadium and phosphorous dissolved in aqueous solution were used as precursors for the process. The products from the flame spray pyrolysis process were found to be hollow and amorphous particles in the range of 2–10 μm with shell thicknesses between 200 and 300 nm. Upon calcination and oxidation, the size of spherical particles grew in diameter and crystallization proceeded. However, the surface of calcined particles showed it was composed of smaller grains in the size range of 0.5–1 μm. Finally, the size dependence stability of different polymorphs of VOPO4 is discussed as well as the effect of the different precursors used to stabilize alpha-II and Beta VOPO4 polymorphs.